2015
DOI: 10.1017/s0033291715002627
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and adults at clinical high-risk for psychosis: age-related differences in attenuated positive symptoms syndrome prevalence and entanglement with basic symptoms

Abstract: APSS status was associated with greater suicidality and illness/psychophathology severity in this help-seeking cohort, emphasizing the need for clinical care. The age-related differences in the prevalence of APSS and the increasing proportion of APSS+/COGDIS+ may point to a higher proportion of non-specific/transient, rather than risk-specific attenuated positive symptoms in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
(55 reference statements)
2
30
0
Order By: Relevance
“…Contrary to brain morphological abnormalities observed in adults at CHR-P (Harrisberger et al, 2016;Walter et al, 2016), structural alterations have not been robustly confirmed in adolescents at CHR-P (Ziermans et al, 2009). These differences may reflect different maturational ages of the brain across these two populations or may alternatively be due to a lower true-positive rate for psychosis in paediatric CHR-P samples due to more nonspecific and overlapping phenomenologies of concurrently emerging psychiatric disorders (Gerstenberg et al, 2015(Gerstenberg et al, , 2016Kelleher et al, 2012;Schimmelmann, Michel, Martz-Irngartinger, Linder, & Schultze-Lutter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to brain morphological abnormalities observed in adults at CHR-P (Harrisberger et al, 2016;Walter et al, 2016), structural alterations have not been robustly confirmed in adolescents at CHR-P (Ziermans et al, 2009). These differences may reflect different maturational ages of the brain across these two populations or may alternatively be due to a lower true-positive rate for psychosis in paediatric CHR-P samples due to more nonspecific and overlapping phenomenologies of concurrently emerging psychiatric disorders (Gerstenberg et al, 2015(Gerstenberg et al, , 2016Kelleher et al, 2012;Schimmelmann, Michel, Martz-Irngartinger, Linder, & Schultze-Lutter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the prevalence of CHR in the clinician-referred samples was 32-42% [33][34][35], which were roughly consistent with each other. While the detection rate in samples of help-seeking individuals ranged from 4.2-80%, which differed from site to site [10,[39][40][41]. As for the general population (primarily focused on young adults and adolescences), the annual incidence of new cases of CHR was estimated to be 1/10 000 [33], and the prevalence was reported to range from 0.3-2.4% [31,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, age was positively correlated to suspiciousness and female sex to unusual perceptual experiences; educational level was positively correlated to unusual thought content and negatively to perceptual abnormalities. These findings are partly surprising and might reflect some sample bias, because it is commonly assumed that age and education will show an inverse correlation with symptom severity or symptom prevalence (Gerstenberg, Theodoridou, Traber‐Walker, et al, ; Ruhrmann et al, ).…”
Section: Introductionmentioning
confidence: 99%